Rain Water Harvesting Sebagai Alternatif Air Bersih Di Desa Maringkik Kabupaten Lombok Timur - Arief Rahman Hakim; Lina Marta Ningsih; Solistiawan (Lembaga Publikasi Ilmiah Nusantara, 2025)
Maringkik Village in East Lombok Regency faces severe clean water limitations due to its geographical condition as a small island with very limited groundwater reserves. This study aims to evaluate the potential of rainwater harvesting (RWH) as a sustainable alternative for clean water provision. The research employed a descriptive-qualitative approach through field observations, household interviews, and annual rainfall data analysis, combined with quantitative calculations of potential rainwater volume based on roof area and laboratory testing of harvested water quality. Results indicate that with an average annual rainfall of 1,500–2,000 mm, each household with a 50 m² roof area can harvest approximately 60–80 m³ of rainwater per year, equivalent to 60–70% of daily household water needs. Laboratory tests revealed that harvested rainwater met clean water standards after undergoing simple treatment using first-flush devices and sand filtration. Community interviews further showed high acceptance levels, with the majority of respondents willing to adopt RWH due to its affordability and environmental benefits. In conclusion, RWH demonstrates significant potential as a technically feasible, economically viable, and socially acceptable solution for enhancing water security in Maringkik Village. Moreover, it serves as an adaptive strategy to climate change challenges for small island and coastal communities.